2019
DOI: 10.1038/s41375-019-0397-9
|View full text |Cite
|
Sign up to set email alerts
|

S100A9-induced overexpression of PD-1/PD-L1 contributes to ineffective hematopoiesis in myelodysplastic syndromes

Abstract: Myelodysplastic syndromes (MDS) are characterized by dysplastic and ineffective hematopoiesis that can result from aberrant expansion and activation of myeloid-derived suppressor cells (MDSCs) within the bone marrow (BM) niche. MDSCs produce S100A9, which mediates premature death of hematopoietic stem and progenitor cells (HSPCs). The PD-1/PD-L1 immune checkpoint impairs immune responses by inducing T-cell exhaustion and apoptosis, but its role in MDS is uncharacterized. Here we report an increased expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
82
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(93 citation statements)
references
References 42 publications
5
82
0
Order By: Relevance
“…One of the promising groups of agents for MDS is checkpoint inhibitors, which has already revolutionized treatment landscape in other malignancies including melanoma, lung cancer, Hodgkin's disease and several others. The results of in vitro and animal studies indicate that early in MDS development inflammatory microenvironment is established in bone marrow [13] leading to pyroptosis of healthy hematopoietic progenitors, activation of myeloid-derived suppressor cells and specific cytokine milieu, which results in overexpression of checkpoint molecules including PD-1/PD-L1 [14] . Nevertheless, the trials of Nivolumab as single agent in MDS did not provide encouraging results [15] .…”
Section: Introductionmentioning
confidence: 99%
“…One of the promising groups of agents for MDS is checkpoint inhibitors, which has already revolutionized treatment landscape in other malignancies including melanoma, lung cancer, Hodgkin's disease and several others. The results of in vitro and animal studies indicate that early in MDS development inflammatory microenvironment is established in bone marrow [13] leading to pyroptosis of healthy hematopoietic progenitors, activation of myeloid-derived suppressor cells and specific cytokine milieu, which results in overexpression of checkpoint molecules including PD-1/PD-L1 [14] . Nevertheless, the trials of Nivolumab as single agent in MDS did not provide encouraging results [15] .…”
Section: Introductionmentioning
confidence: 99%
“…MDSCs express high levels of PD-L1 to restrain anti-tumour T-cell response. This upregulation of PD-L1 expression has been associated with the S100A9 inflammatory protein and HIF1α [167,188]. In addition, overexpression of PD-L1 has also been reported to induce aberrant hematopoiesis [188].…”
Section: Immunosuppression Of Mdscmentioning
confidence: 95%
“…This upregulation of PD-L1 expression has been associated with the S100A9 inflammatory protein and HIF1α [167,188]. In addition, overexpression of PD-L1 has also been reported to induce aberrant hematopoiesis [188]. Another mechanism employed by MDSCs to suppress T-cell activity is through the recruitment of Tregs by the expression of immune stimulatory receptor CD40 on MDSCs [87].…”
Section: Immunosuppression Of Mdscmentioning
confidence: 99%
“…High expression of PD-L1 in pancreatic cancers is associated with a poor prognosis [24]. According to published reports, S100A8 and S100A9 can induce the expression of PD-L1 in macrophages [28,47]. Therefore, we examined the effect of S100A9 on monocytes and found that S100A9 not only had chemotactic effects but could also induce surface expression of PD-L1 in monocytes.…”
Section: Discussionmentioning
confidence: 95%
“…In addition to its chemotactic effect, S100A9 has been reported to be the endogenous ligand of Toll-like receptor 4 (TLR4) and to induce surface expression of PD-L1 in primary hematopoietic cells [28,29]. High expression of PD-L1 in PDAC was associated with poor prognosis [30]; however, the mechanism that regulates the expression of PD-L1 in PDAC is not clear.…”
Section: S100a9 Induces Surface Expression Of Pd-l1 In Monocytesmentioning
confidence: 99%